Dangal : Cinematic Representation of Competitive Marketing Strategy - Dutta, Nirankush; Bhat, Anil K. (Prabandhan: Indian Journal of Management, 2017)
Directed by Nitesh Tiwari and starring Aamir Khan, Dangal is an Indian Hindi language biographical sports drama, which emerged as the first mainstream Hindi film to cross the ` 350 crores mark. The movie presents a lot of lessons pertaining to social values, human resources, and competitive marketing strategies, when different scenes are used as similes. This article discussed the scenes of the film from the perspective of competitive marketing strategies for challengers, taking cues from Adam Morgan's Eating the Big Fish and those pointed out by Philip Kotler. In doing so, this article provided an in-depth analysis of the film, which may be of immense value to management trainers and marketing educators in their attempt to explain difficult concepts of management and marketing in a lucid language comprehensible by a large audience.